SEM with simplicity and accuracy - Bentler, Peter M. (2010)
Professor Iacobucci has provided a useful introduction to the computer program LISREL, as well as to several technical topics in structural equation modeling (SEM). However, SEM has not been synonymous with LISREL for several decades, and focusing on LISREL’s 13 Greek matrices and vectors is not the most intuitive way to learn SEM. It is possible today to do model specification via a path diagram without any need for filling in matrix elements. The simplest alternative is based on the Bentler–Weeks model, whose basic concepts are reviewed. Selected additional SEM topics are discussed, including some recent developments and their practical implications. New simulation results on model fit under null and alternative hypotheses are also presented that are consistent with statistical theory but in part seem to contradict those reported by Iacobucci.